2015
DOI: 10.1007/s11095-015-1811-2
|View full text |Cite
|
Sign up to set email alerts
|

The Interesting Case of Acyclovir Delivered Using Chitosan in Humans: Is it a Drug Issue or Formulation Issue?

Abstract: The choice of the drug and the formulation type intended to deliver the drug need to be made in a diligent and pragmatic fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This caused the biopolymer to have a minimal impact on the Caco-2 monolayer integrity, leading to no enhancement in the absorption of acyclovir [83]. This was further corroborated by a recent study that concluded that the absorption-enhancing effect of chitosan was drug-dependent, with acyclovir displaying unfavorable enhancement of absorption in the presence of chitosan [84]. On the other hand, there are studies that highlighted drugs that displayed an enhanced absorption with the aid of chitosan, and these include molecules such as buserelin, [ 14 C] mannitol, and dextran [79,85].…”
Section: Chitosanmentioning
confidence: 64%
“…This caused the biopolymer to have a minimal impact on the Caco-2 monolayer integrity, leading to no enhancement in the absorption of acyclovir [83]. This was further corroborated by a recent study that concluded that the absorption-enhancing effect of chitosan was drug-dependent, with acyclovir displaying unfavorable enhancement of absorption in the presence of chitosan [84]. On the other hand, there are studies that highlighted drugs that displayed an enhanced absorption with the aid of chitosan, and these include molecules such as buserelin, [ 14 C] mannitol, and dextran [79,85].…”
Section: Chitosanmentioning
confidence: 64%